University intellectual property commercialization: A critical review of literature - Mohamad Sharif, Sabri; Ahamat, Amiruddin; Abdullah, Mariam Miri; Jabar, Juhaini; Bakri, Mohammed Hariri (Istanbul Kültür University, 2018)
Universities have specialized facilities and experts to support innovation system of a country. Despite the fact that these facilities are being properly utilized at the university level, there are several factors that influence university-led innovation, thus creation of intellectual properties. Some of the highly sought-after innovations are significantly profitable for number of universities. Given that the funding to universities are reducing globally, universities and policymakers would like to utilize these innovations to fund university activities. This study critically reviews the factors that determine the success in university-led IP commercialization to shed light on how the benefit from innovation can be achieved.